Hubungan Tinggi Lompatan dan Kekuatan Lengan terhadap Akurasi Smash Bola Voli - Alfiah Rizqi Azizah; Sekar Nun Soleha (Departement of Mathematics Education, 2024)
The low smash ability of male volleyball players at SMP Negeri 2 Karanggayam is a problem in this research. This research is a type of correlation research which aims to determine the relationship between jump height (X1) and arm strength (X2) as two independent variables on smash accuracy (Y) in volleyball as the dependent variable. The research population was volleyball extracurricular participants at SMP Negeri 2 Karanggayam. This sampling was carried out using a purposive sampling technique, totaling 20 male players participating in extracurricular activities at SMP Negeri 2 Karanggayam. Data were collected by measuring arm muscle strength using a spring balance, and jump height using a vertical jump test. Next, smash accuracy is carried out using a smash accuracy test. Data analysis and testing of hypotheses 1 and 2 used simple correlation analysis, while hypothesis 3 used multiple correlation analysis techniques with a significance level of α = 0.05. Based on the data analysis, the following results can be obtained: (1) There is a significant relationship between the strength of the height of the jump and the accuracy of the smash, with a correlation coefficient of 0.467. (2) There is a significant relationship between jump height and smash accuracy with a correlation coefficient of 0.555. (3) There is a significant relationship between high jump strength and arm strength simultaneously on smash accuracy.